2022
DOI: 10.1002/fes3.321
|View full text |Cite
|
Sign up to set email alerts
|

Integrated farming system approaches to achieve food and nutritional security for enhancing profitability, employment, and climate resilience in India

Abstract: Integrated farming systems (IFS) entail a holistic approach to farming aimed at meeting the multiple demands (impart farm resilience, farmer livelihoods, food security, ecosystem services, and making farms adaptive and resilient, etc.). IFS are characterized by temporal and spatial mixing of crops, livestock, fishery, and allied activities in a single farm. It is hypothesized that these complex farms are more productive at a system level, are less vulnerable to volatility, and produce less negative externaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…In traditional agrarian regions, rural farmers are highly dependent on public forest resources such as fooder, fuel wood, building materials, etc. because they have an integrated farming system among cultivated land, livestock, and forest resources (Jha & Bawa 2006, Paramesh et al 2022, Wenhua & Min 1999. The mountain and hills of Nepal have a traditional intensive subsistence farming system and the majority and most of them are still in the same condition.…”
Section: Ndvi Changes By Built-up Densitymentioning
confidence: 99%
“…In traditional agrarian regions, rural farmers are highly dependent on public forest resources such as fooder, fuel wood, building materials, etc. because they have an integrated farming system among cultivated land, livestock, and forest resources (Jha & Bawa 2006, Paramesh et al 2022, Wenhua & Min 1999. The mountain and hills of Nepal have a traditional intensive subsistence farming system and the majority and most of them are still in the same condition.…”
Section: Ndvi Changes By Built-up Densitymentioning
confidence: 99%
“…Most spawnings in rice fields produce glue-like eggs that are generally arranged on green plants to provide extra oxygen and nutrition designed for maturing embryos (AL-Kattan et al, 2019;Al-Rejaboo & Jalaluldeen, 2019;Falya et al, 2021). However, shallow water net constructors and spawners breed in paddy fields under ideal conditions) (Paramesh et al, 2022).…”
Section: Objectives Of Integrated Farmingmentioning
confidence: 99%
“…The flower plantation like Rose, Jasmine, Gladiolus, Marigold and Chrysanthemum on the embankment is also provides additional income to the farmer and besides aiding beauty to the farm. Farmers depending intensive agriculture on single farm enterprise in India are unable to sustain their livelihood, but the integration of crops, livestock, fishery components enable them to sustain food, and nutritional security with regular and periodic income round the year (Paramesh et al, 2022, Yadav et al, 2022. Kumar et al (2012) demonstrated that enhancement of the productivity of resources, economic returns, generating employment and maintaining soil health of farm can be achieved by the combination of crop, fish, duck and goat at low-laying lands of Bihar instead of cultivating crop alone on same piece of land under irrigated condition.…”
Section: Adoption Of Integrated Fish Farmingmentioning
confidence: 99%
“…T he fisheries sector contributes significantly to the Indian socio-economic, nutritional security and foreign exchange (Lokesh and Khidrapure, 2016, Sharma et al, 2019, Suguna, 2020, Ngasotter et al, 2020, Chand and Prasad, 2021 and sector shares 1.07% and 5.30% to the national and agricultural GDP, respectively (Rajani and Balasubramanian, 2021). Average size of operating land holding in Indian farmers is reducing continuously due to outcome of subdivision of property across generations and also India's policies (Kumar et al, 2012, Kumar and Sharma, 2020, Giller et al, 2021, Balkrishna et al, 2022, Paramesh et al, 2022, limits horizontal expansion of aquaculture ponds. But, aquaculture grows at an astonishing rate of 46.8% due to its technological advancement (Sarkar et al, 2019, Suguna, 2020, Chand and Prasad, 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation